ORGANIZATIONAL COMMITMENT OF HEADS OF DEPARTMENTS OF MUHAMMADIYAH'S HIGHER EDUCATION INSTITUTIONS IN KOPERTIS (PRIVATE HIGHER EDUCATION COORDINATOR) REGION III - Sitorus, Onny Fitriana; Putrawan, I Made; Abdullah, Thamrin (JERAM, 2017)
The purpose of this research is to obtain information about organizational commitment of heads of departments of Muhammadiyah’s Higher Education Institutions in Kopertis Region III, which is influenced by cognitive ability, transformational leadership, and organizational justice. The research was conducted using quantitative approach with the path analysis method in hypothesis testing. In this study, where heads of departments are as the unit of analysis, 53 samples of heads of departments were obtained and selected at random. The results of the study were as follows: (1) cognitive ability has a direct positive effect on organizational commitment; (2) transformational leadership has a direct positive effect on organizational commitment; (3) organizational justice has a direct positive effect on organizational commitment; (4) cognitive ability has a direct positive effect on organizational justice; (5) transformational leadership has a direct positive effect on organizational justice; (6) cognitive ability has a direct positive effect on transformational leadership. Based on these findings, it can be concluded that cognitive ability, transformational leadership, organizational justice can increase organizational commitment of the heads of departments of Muhammadiyah’s Higher Education Institutions in Kopertis Region III.